SMART DOOR LOCK SYSTEM DEVELOPMENT PROTOTYPE USING RFID TECHNOLOGY ID-12 - Siti Aisyah; Yusmar Ali; Komda Saharja; Asrul Sani (Kresnamedia Publisher, 2022)
This smart door lock system is intended to make it easier to control security in specific homes or rooms, such as government offices or factories, to prevent unauthorized entry into a small space. This automatic door lock system includes an ID-12 RFID reader, tag/transponder, Arduino UNO R3, 5v buzzer, drop bolt lock, relay module, and LCD. This ID-12 RFID reader functions as both a receiver and a transmitter. RFID improves system performance by enhancing information acquisition and remote digital archiving. This research aims to develop RFID-based technology by combining it with current information technology development. Contribute to the advancement of scientifically based digital technology.